Der Kirchenkampf : the Gutteridge-Micklem collections - Gutteridge, Richard; Micklem, Nathaniel, 1888- (K.G. Saur, 1987)
Microfilm reproduction of theological and political documents (dated from 1930 to 1969) that include books, periodicals, pamphlets, correspondence, reports, memoranda and manuscripts relating to the struggle of the German Evangelical Church against the Nazis' attempt to impose a unified Reichskirche (State Church) and to the struggle within the church to define its own development and structure.